Engaging Indonesian students in “read, reread, list, compose” strategy to enhance paraphrasing skill - Tatin Yuliani; Nia Kurniawati; Predari Siswayani (Journal of Education and Learning (EduLearn), 2023)
One crucial skill to master by university students related to academic writing activity is paraphrasing skill. However, in Indonesian context, the university students still find paraphrasing challenging. Therefore, this study is intended to explore the use of read, reread, list, compose (RRLC) strategy to enhace the students’ paraphrasing skill in a college context. This study utilizes a qualitative case study design where the data were obtained through observation. The study revealed that RRLC stages can be implemented in learning activity. It engaged the students in activating their prior knowledge, doing an independent reading, discussing, and sharing their understanding about the text before paraphrasing. It assisted them to have better comprehension of the text to be paraphrased. In addition, during the implementation of composing stage in guided practice, the students’ paraphrased works indicated that the students were able to create sentences in different structures—active or passive constructions, use the synonyms, and retain the original meaning. These three skills helped them reduce the similiarity of their paraphrased works from the original version. This study recommends that RRLC strategy be implemented in teaching paraphrasing at college or lower level with some adjustments to meet the students’ basic English skill.